Gamification in the Educational Context: A Systematic Mapping of Literature with a Focus on the Evaluation of Gamification - Souto Reinheimer, Wendel; Duarte Medina, Roseclea (RENOTE, 2021)
Gamification has been a strategy widely used in the educational field to promote learning, engage and motivate students. Despite this, studies point to some issues related to the evaluation process in educational contexts. Thus, this work aims to identify the state of the art of evaluation in educational contexts. To this end, a systematic mapping of the literature was conducted. In total, 106 (one hundred and six) works were analyzed. As a result, a very heterogeneous scenario was found in the gamification evaluation process. Most authors carry out the evaluation of gamification in non-experimental studies; among the most used instruments are questionnaires. Regarding the observed metrics, most studies investigate metrics related to learning/performance, participation/interaction and metrics collected based on the opinion/perception of the participants.